Bronchotracheal Stenting Management by Rigid Bronchoscopy under Extracorporeal Membrane Oxygenation (ECMO) Support: 10 Years of Experience in a Tertiary Center - Sabrina Meyer; Anne-Sophie Dincq; Lionel Pirard; Sebahat Ocak; Jean-Paul D’Odémont; Philippe Eucher; Benoît Rondelet; André Gruslin; Laurie Putz (Canadian Respiratory Journal)
Purpose. Airway stenting offers good palliation and improves the quality of life in patients with inoperable bronchotracheal stenosis. However, in some cases, the management of stenting can be life-threatening. Hence, a strategy for maintaining oxygenation and hemodynamic stability should be anticipated to avoid critical situations. Herein, we report the use of extracorporeal membrane oxygenation (ECMO) in bronchotracheal stenting management to secure oxygenation and facilitate interventions. Methods. We retrospectively reviewed all patients who underwent rigid bronchoscopy under ECMO support for the management of bronchotracheal stenting at CHU UCL Namur hospital (Belgium), between January 2009 and December 2019. Results. We included 14 bronchoscopy cases performed on 11 patients (3 patients underwent 2 bronchoscopies) in this study; 12 were performed on males and 2 on females. The median age was 54 years. There were 11 benign and 3 malignant etiologies for the central airway obstruction/stenosis. Eight cases were supported by venovenous ECMO and six by venoarterial ECMO. The median ECMO time was 267 minutes. The weaning of ECMO support was successful in all cases. In most cases, the procedures were performed effectively and safely. Only two local complications caused by the cannulation of ECMO were reported, and anticoagulation was adapted to avoid bleeding at the operating site and clot formation in the system. Conclusion. Elective ECMO support was helpful and safe for the high-risk management of bronchotracheal stenting with rigid bronchoscopy and was not associated with any additional significant complications.